2022
DOI: 10.3390/ijerph19137713
|View full text |Cite
|
Sign up to set email alerts
|

Family Alliance and Intergenerational Transmission of Coparenting in Gay and Heterosexual Single-Father Families through Surrogacy: Associations with Child Attachment Security

Abstract: Parents tend to internalize the coparenting model they experienced during childhood and enact it in their coparenting relationships as adults. These interactive patterns may, in turn, shape their children’s internal working models of attachment relationships. The present study recruited 31 gay and 28 heterosexual single-father families through surrogacy to examine family alliance quality and the mediating role of observed supportive and conflictual coparenting in the association between the coparenting quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Regardless of family type, lower supportive parenting and sensitivity foretold better father-reported child internalizing problems, while lower sensitivity and rough-and-tumble play quality, more negative parenting and parenting stress, and the male gender of the child predicted greater father-reported child externalizing problems [ 23 ]. Moreover, single fathers who felt more coparenting positive experiences within their families of origin exhibited lower levels of conflictual coparenting, which were, in turn, associated with better child attachment security [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of family type, lower supportive parenting and sensitivity foretold better father-reported child internalizing problems, while lower sensitivity and rough-and-tumble play quality, more negative parenting and parenting stress, and the male gender of the child predicted greater father-reported child externalizing problems [ 23 ]. Moreover, single fathers who felt more coparenting positive experiences within their families of origin exhibited lower levels of conflictual coparenting, which were, in turn, associated with better child attachment security [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the investigation studying single-father families’ interactions and the psychosocial adjustment of children born via surrogacy, have demonstrated that these families are well adjusted and function well [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Far fewer studies have been implemented with children born via surrogacy than on families with children formed through other more recurrent procedures of reproduction [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Additionally, the current understanding of this these families is largely based on the experiences of white Italian, Israeli or American men who have the emotional and financial availability to pursue surrogacy.…”
Section: Discussionmentioning
confidence: 99%
“…In his study on Italian gay and heterosexual single fathers by choice through surrogacy, who coparent with nonparental caregivers (e.g., grandparents, babysitters, uncles/aunts), Carone [ 42 ] considers the impact of intergenerational transmission of coparenting on child attachment security. His findings indicate that fathers who were exposed to higher coparenting quality in their families of origin exhibit lower levels of conflictual coparenting with the nonparental caregiver, which, in turn, is associated with their children’s attachment security.…”
Section: Single-parent-by-choice Familiesmentioning
confidence: 99%
“…There has been little focus on parenting and child development in single- and trans*-parent families created by ARTs, though the preliminary evidence on children in early and middle childhood indicates that neither the number of parents nor parents’ gender identities result in negative outcomes [ 17 , 18 , 19 , 20 , 21 ]. However, some studies have shown that a single-father family structure created by surrogacy and parental gender identity are, in some cases, relevant to parents’ and children’s external experiences, including their exposure to microaggressions and negative attitudes from others [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%